Grow cook eat : a food lover's guide to vegetable gardening : including how to grow 50 vegetables, herbs, and fruits - Galloway, Willi (Sasquatch Books, 2025)
"The conscious foodie's guide to growing and harvesting their own urban vegetable garden--featuring 50 profiles of common vegetables and herbs, plus 50 recipes for garden-to-table meals you'll want to make again and again"--